Candida guilliermondii as an agent of postpartum subacute mastitis in Rio de Janeiro, Brazil: Case report - Pinto, Tatiane Nobre; Kohn, Alana; da Costa, Gisela Lara; Oliveira, Laura M. A.; Pinto, Tatiana C. A.; Oliveira, Manoel M. E. (Frontiers in Microbiology, 2022)
Candida spp. can cause mild to severe human infections. Certain species have been described as the etiologic agent of human mastitis. Mastitis affects millions of lactating women and can be a source of disease transmission to the infant. In this work we report of the detection of a Candida guilliermondii isolate from the milk of a puerperal woman with subacute mastitis, being the first description of human mastitis caused by Candida guilliermondii in Rio de Janeiro, Brazil.